THE DETECTION OF PROPERTIES OF FUNCTIONS OF ECONOMIC ANALYSIS WITH THE SUPPORT OF INFORMATION TECHNOLOGY - ORSZAGHOVA, Dana (Trends in education, 2014)
Functions of economic analysis with one or more real variables are proper means for formulation of relations among economic variables by quantitative methods in the area of business market and production sphere. In this paper we deal with the important topic of mathematics study - various properties of functions and their graphs illustration by tools of information technology (IT). We present economic applied samples with properties and graphs for a function with one variable and for a function with two variables. Solving of practical and applied problems is a current trend which is noticed in mathematical education. Graphical tools of IT support efficient drawing of graphs of functions and improve possibilities for interpretation and better understanding of results of solved tasks by students.
Keywords: mathematics; functions; properties of functions; economic application; graphs of functions; information technology.